Manifestations of rationality and faith in models of Andalusian poetry (Journal of Misan Researches, 2020)
The study aims at summarizing some of the two poetic texts of Andalusian Literature in terms of idealistic faith in these texts. The study shows, after introducing the idealistic aspect of the languages, some features that are shown in these texts .They show the interaction of peace and religion. These two trends are clearly evident in the first centuries when the Andalusian literature used social criticism and opposing oppressive rulers presented in Andalusia literature. The study also aims at displaying some texts that deal with reforming features and how poets are concerned with some of the social issues. They are, in this regard, responsible for reforming societies and making changes. It further, presents some texts that have religious perspectives which appeared in most of the idealistic poetry of Andalusia. And some of these themes are concerned with issues like death and mortality and how are these themes related to God. In these texts, God is described as the most powerful who can change but it never changed. The study is concerned with idealistic poetry of different poets who belong to the literature of Andalusia.